IMMUNOTHERAPY IN TREATMENT OF ANAPLASTIC THYROID CANCER: A CASE REPORT - Kostadinova, Lenche; Petrova, Deva; Ilova, Marija Karakolevska (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
This case report describes a 55-year-old woman with diagnosed anaplastic thyroid cancer (ATC). Initially, the patient was treated surgically, followed by rapid progression. After that radiation therapy was performed, and the patient immediately progresses again. It was decided that the patient should start chemotherapy while waiting for molecular tests due to the rapid growth of the cancer. After six cycles of chemotherapy in which the disease was stable progression occurred again immediately after discontinuation of chemotherapy. Molecular test shows PD-L1 positive patient with CPS score of 20% and she was put on immunotherapy with pembrolizumab. After 1 year of immunotherapy treatment, PET CT scan showed metabolic and morphological regression of tumor mass in the neck and cervical lymph nodes. The patient had a good quality of life with no side effects throughout the immunotherapy. In this case, we want to emphasize that immunotherapy can also be considered  as choice of treatment in anaplastic thyroid carcinoma who represents carcinomas with  high lethality rate. Keywords: thyroid anaplastic carcinoma, immunotherapy, PD-L1, pembrolizumab.